PENGARUH TOTAL ASSET TURNOVER (TATO), RETURN ON ASSET (ROA), DAN DEBT TO ASSET RATIO (DAR) TERHADAP PRICE TO BOOK VALUE (PBV) PADA PERUSAHAAN SUBSEKTOR RETAILING YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Ridha Nurhuda; Dian Wahyuni (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to determine whether TATO, ROA, and DAR simultaneously and partially influence PBV in companies in the retail subsector listed on the Indonesia Stock Exchange. This is a descriptive quantitative study. Data analysis in this study employed multiple linear regression using SPSS for Windows software. Based on the F-test results, it is shown that the variables TATO, ROA, and DAR collectively have an effect on PBV with a significance value of 0.000 (0.000 < 0.05) and a calculated F-value greater than the critical F-value (11.031 > 2.87). The t-test results indicate that TATO has a significance value of 0.255 > 0.05 with a t-calculated value < t-table (-1.157 < 2.030), meaning TATO does not influence PBV. ROA shows a significance value of 0.000 < 0.05 with a t calculated value > t- table (4.425 > 2.030), meaning that ROA has an effect on PBV. DAR shows a significance value of 0.001 < 0.05 with a calculated t-value > table t-value (3.549 > 2.030), meaning that DAR has an effect on PBV. The results of the coefficient of determination (R²) test show an Adjusted R² value of 0.432, or 43.2%. This indicates that the independent variables (TATO, ROA, and DAR) account for 43.2% of the variation in the dependent variable, PBV. Keywords: Total Asset Turnover (TATO), Return on Assets (ROA), Debt to Asset Ratio (DAR), and Price to Book Ratio (PBV)   Abstrak: Penelitian ini bertujuan untuk mengetahui apakah TATO, ROA, dan DAR secara simultan dan parsial berpengaruh terhadap PBV Pada Perusahaan Subsektor Retailing Yang Terdaftar di Bursa Efek Indonesia. Jenis penelitian ini adalah penelitian kuantitatif yng bersifat deskriptif. Analisis data dalam penelitian ini menggunakan analisis regresi linier berganda dengan meggunakan software SPSS for windows. Berdasarkan hasil uji F menunjukkan bersama-sama variabel TATO, ROA, dan DAR mempunyai pengaruh terhadap PBV dengan hasil nilai signifikansi 0,000 (0,000 < 0,05) dengan nilai  >  (11,031 > 2,87). Hasil uji t diketahui bahwa TATO mempunyai nilai signifikansi sebesar 0,255 > 0,05 dengan nilai <  (-1,157 < 2,030), artinya TATO tidak berpengaruh terhadap PBV. ROA menunjukkan nilai signifikansi sebesar 0,000 < 0,05 dengan nilai  >  (4,425 > 2,030), artinya ROA berpengaruh terhadap PBV, DAR menunjukkan nilai signifikansi sebesar 0,001 < 0,05 dengan nilai  >  (3,549 > 2,030), artinya DAR berpengaruh terhadap PBV. Hasil uji koefisien determinasi (), nilai nilai Adjusted R square sebesar 0,432 atau 43,2%. Hal ini menunjukkan bahwa 43,2% kemampuan variabel independen (TATO, ROA, dan DAR) untuk menjelaskan variabel dependen yaitu PBV. Kata Kunci: Total Asset Turnover (TATO), Return On Asset (ROA), Debt to Asset Ratio (DAR), dan Price to Book Value (PBV)